Biofunctool®: a new framework to assess the impact of land management on soil quality. Part B: investigating the impact of land management of rubber plantations on soil quality with the Biofunctool® index. (February 2019) - Thoumazeau, Alexis; Bessou, Cécile; Renevier, Marie-Sophie; Panklang, Phantip; Puttaso, Porntip; Peerawat, Monrawee; Heepngoen, Pusanisa; Polwong, Prapatsorn; Koonklang, Nitjaporn; Sdoodee, Sayan; Chantuma, Pisamai; Lawongsa, Phrueksa; et al.
Graphical abstract: Highlights: A new soil quality index aggregating the set of Biofunctool ® indicators was created. The Biofunctool ® index was applied in rubber tree-based cropping systems. The Biofunctool ® index proved to be sensitive to land uses and management practices. The Biofunctool ® index proved to be robust against various pedo-climatic contexts. The Biofunctool ® index allows to characterize a gradient of soil disturbance. Abstract: Biofunctool ® is a new framework for assessing the impact of land management on soil quality – defined as the capacity of the soil to function. Biofunctool ® uses a set of twelve indicators to monitor changes in three key soil functions: carbon transformation, nutrient cycling and structure maintenance (part A). Information from all the indicators is integrated in a Soil Quality Index using multivariate analysis (PCA) weighting. We used Biofunctool ® to assess the impact of land use, land use change and agricultural practices on soil quality. The Biofunctool ® index was measured for soils in Thailand within rubber plantations, forests and intensive cash crops (cassava and sugar cane). The results demonstrate that the Biofunctool ® index provides an aggregated synthetic soil functioning score that is sensitive to land management and is robust in various pedo-climatic contexts. Firstly, the index revealed the impact on soil of land conversion from annual cropping to rubber plantations and ranked the effect on soil with respect to a natural forest reference. Secondly, it showed the positive effect of legume cover-crops on soil functioning. Thirdly, it highlighted a trend of improving soil quality with increasing age of rubber plantations, in contrasted pedo-climatic contexts. It is concluded that the Biofunctool ® index is a reliable and relevant descriptor of integrated soil functioning (i.e. soil quality) that could be useful for environmental impact assessment at regional to global scales.